Agricultural Development, Commercialization, and Job Creation: Does Foreign Investment Matters in Nepal? - Basu Dev Lamichhane, (Interdisciplinary Journal of Management and Social Sciences, 2022)
In the field of agricultural output and job generation, foreign investment in the agricultural sector in Nepal has become a hot topic. This was a review article. The relevant literature has been reviewed for the purposes of the study. The bulk of Nepalese people works in agriculture and lives in rural areas. The agriculture industry has played a significant role in the growth of Nepal's GDP and economic development. Agricultural occupation has dominated the business and service sectors. The characteristics of Nepalese agro-economics were also investigated in this paper. The study found that FDI in the agricultural sector contributed to job creation, technology transfer, access to the international market for agro-products, skill development, earning foreign exchange, fostering economic development, food security, upgrading local businesses, utilizing local natural and human resources, commercialization and modernization of the agricultural sector, social peace and stability, and controls over brain-drain. Agriculture has historically been a powerful source of employment and poverty reduction. The sector has played an important role in promoting employment in rural and semi-rural areas. Low agro-investment has resulted in lower profitability, competitiveness, and low government revenue.